Shared genetic variance between obesity and white matter integrity in Mexican Americans - Spieker, Elena A.; Kochunov, Peter; Rowland, Laura M.; Sprooten, Emma; Winkler, Anderson M.; Olvera, Rene L.; Almasy, Laura; Duggirala, Ravi; Fox, Peter T.; Blangero, John; Glahn, David C.; Curran, Joanne E. (Frontiers in Genetics, 2015)
Obesity is a chronic metabolic disorder that may also lead to reduced white matter integrity, potentially due to shared genetic risk factors. Genetic correlation analyses were conducted in a large cohort of Mexican American families in San Antonio (N=761, 58% females, ages 18-81y; 41.3±14.5) from the Genetics of Brain Structure and Function Study. Shared genetic variance was calculated between measures of adiposity ((body mass index (BMI; kg/m2) and waist circumference (WC; in)) and whole-brain and regional measurements of cerebral white matter integrity (fractional anisotropy). Whole-brain average and regional fractional anisotropy values for ten major white matter tracts were calculated from high angular resolution diffusion tensor imaging data (DTI; 1.7×1.7×3 mm; 55 directions). Additive genetic factors explained intersubject variance in BMI (heritability, h2=0.58), WC (h2=0.57), and FA (h2=0.49). FA shared significant portions of genetic variance with BMI in the genu (ρG = -0.25), body (ρG = -0.30), and splenium (ρG = -0.26) of the corpus callosum, internal capsule (ρG = -0.29), and thalamic radiation (ρG = -0.31) (all p’s = .043). The strongest evidence of shared variance was between BMI/WC and FA in the superior fronto-occipital fasciculus (ρG = -0.39, p = .020; ρG = -0.39, p = .030), which highlights region-specific variation in neural correlates of obesity. This may suggest that increase in obesity and reduced white matter integrity share common genetic risk factors.